A hope unburied [large type] - Woodhouse, Kimberley, 1973- (Woodhouse, Kimberley, 1973- Treasures of the Earth, 2025)
"In 1916, Eliza Mills defies societal expectations to pursue her passion. Having published her early groundbreaking papers under a false name, she has finally earned the opportunity to work with a renowned paleontologist. But when Eliza gets the chance to dig up bones at a ranch with a dark history, it sparks a chain of events that will rock the very fabric of her world. Devin Schmitt, Eliza's closest friend, agrees to visit her. Within a few days of his arrival, he and Eliza find themselves entangled in a web of danger. Together, Devin and Eliza must unbury the truth and save Eliza from those who wish to see her fail." -- Page [4] cover.